The effect of additional breathing exercises in postural training on decreasing the hyperkyphosis curve in the elderly - Ilmanisa; Muthiah Munawwarah; Kesit Ivanali; Trisia Lusiana Amir (Universitas Udayana dan Diaspora Taipei Medical University, 2023)
Background: Elderly is someone who is classified as old and is experiencing the aging process. The risk of falling and decreased function are two of the many geriatric syndromes, which are affected by various things, such as muscle weakness, imbalance, and poor posture. Objective: This study aimed to determine the difference in the effect of adding deep breathing exercises on postural training and only postural training on reducing the hyperkyphosis curve. Methods: This study is quasi-experimental with a pre-test and post-test group design, in which the thoracic kyphosis curve is measured with a flexible ruler. The total sample in this study was 22 people divided into two groups. Group 1 consisted of 11 people with the intervention given, namely postural training, and group 2 consisted of 11 people with the intervention given, namely postural training and deep breathing exercise. Results: Hypothesis testing I and II using the Paired sample t-test showed a value of p=0.000, with an average value before and after in group 1 of 54.17 ± 2.39 and 50.90 ± 2.43, while in group 2, it was 54.61 ± 2.07 and 50, 11±1.93. Furthermore, Hypothesis testing III used the Mann Whitney-u tried and obtained a value of p=0.000 with a difference in group 1 of 3.26 ± 0.57 and group 2 of 4.50 ± 0.41. Conclusion: There is a significant difference in effectiveness with the addition of breathing exercises in postural training and postural training alone in reducing the hyperkyphosis curve.